Ceramic petrography : the interpretation of archaeological pottery & related artefacts in thin section - Quinn, Patrick S. (Archaeopress, 2013)
Thin section ceramic petrography is a versatile interdisciplinary analytical tool for the characterization and interpretation of archaeological pottery and related artefacts, including ceramic building materials, refractories and plaster. Using over 200 colour photomicrographs of thin sections from a diverse range of artefacts, archaeological periods and geographic regions, this book illustrates the spectrum of compositional and microstructural phenomena that occur within ancient ceramics under the micro-scope and provides comprehensive guidelines for their study within archaeology. The book is structured according to the main steps involved in the analysis and interpretation of archaeological ceramic thin sections, including classification, characterization, the determination of provenance and the reconstruction of manufacturing technology.